Sustainable Synthesis of Adipic Acid via MnOx-Catalyzed Electrooxidation of Cyclohexanol in Neutral Electrolyte - Jiaming Shi; Guiling Zhang; Shiying Yang; Dan Yang; Yuguang Jin; Xiaoyue Wan; Yihu Dai; Yanhui Yang; Chunmei Zhou (Molecules)
Adipic acid (AA), a pivotal precursor for nylon-6,6 and polyurethane, was synthesized via an innovative catalytic electrocatalytic oxidation strategy in this study. Four distinct MnOx/CNT nanocatalysts were prepared by hydrothermal and co-precipitation methods and fabricated into electrodes for the oxidation of cyclohexanol (Cy-OH) in a K2SO4 neutral solution. Comprehensive characterization revealed that the catalytic performance depended on both crystalline phase configuration and manganese valence states. MnO(OH) and MnOx were identified as the main active species, with the synergy between MnO species and carbon nanotubes significantly enhancing catalytic activity. Mechanistic investigations demonstrated that under Mn4+-dominant conditions, low-valence manganese species facilitated Cy-OH-to-cyclohexanone (Cy=O) conversion, while an optimal Oads/Olat ratio (≈1) effectively promoted subsequent Cy=O oxidation to AA. Under optimized conditions (1.25 V vs. Ag/AgCl, 80 °C, 15 h), complete Cy-OH conversion was achieved with 56.4% AA yield and exceptional Faradaic efficiency exceeding 94%. This work elucidates manganese-based electrocatalytic oxidation mechanisms, proposes a sequential reaction pathway, and establishes an environmentally benign synthesis protocol for AA, advancing sustainable industrial chemistry.